The Type III Secretion Effector CteG Mediates Host Cell Lytic Exit of Chlamydia trachomatis - Pereira, Inês Serrano; Pais, Sara Vilela; Borges, Vítor; Borrego, Maria José; Gomes, João Paulo; Mota, Luís Jaime (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis is an obligate intracellular bacterium causing ocular and urogenital infections in humans that are a significant burden worldwide. The completion of its characteristic infectious cycle relies on the manipulation of several host cell processes by numerous chlamydial type III secretion effector proteins. We previously identified the C. trachomatis CteG effector and showed it localizes at the host cell plasma membrane at late stages of infection. Here, we showed that, from 48 h post-infection, mammalian cells infected by wild-type C. trachomatis contained more infectious chlamydiae in the culture supernatant than cells infected by a CteG-deficient strain. This phenotype was CteG-dependent as it could be complemented in cells infected by the CteG-deficient strain carrying a plasmid encoding CteG. Furthermore, we detected a CteG-dependent defect on host cell cytotoxicity, indicating that CteG mediates chlamydial lytic exit. Previous studies showed that Pgp4, a global regulator of transcription encoded in the C. trachomatis virulence plasmid, also mediates chlamydial lytic exit. However, by using C. trachomatis strains encoding or lacking Pgp4, we showed that production and localization of CteG are not regulated by Pgp4. A C. trachomatis strain lacking both CteG and Pgp4 was as defective in promoting host cell cytotoxicity as mutant strains lacking only CteG or Pgp4. Furthermore, CteG overproduction in a plasmid suppressed the host cell cytotoxic defect of CteG- and Pgp4-deficient chlamydiae. Overall, we revealed the first chlamydial type III secretion effector involved in host cell lytic exit. Our data indicates that CteG and Pgp4 participate in a single cascade of events, but involving multiple layers of regulation, leading to lysis of host cells and release of the infectious chlamydiae.